Komunikasi Lintas Agama dalam Menciptakan Kerukunan Bermasyarakat di Kelurahan Air Jamban - Septiani; Fajri Ahmad (Bahasa Indonesia, 2024)
This research is based on the problem that there is a religious conflict in Air Jamban Village between Muslims and Christians caused by the ineffectiveness of the communication conveyed. So that it has an impact on community life and can cause divisions between religious people, one of which is a problem that occurs due to misunderstandings that almost cause provocations between religious people. This research method uses qualitative research with a field approach and is described in a qualitative descriptive manner. This research applies data collection techniques, namely observation, interviews and documentation. The results of the study show that interfaith communication carried out between Muslims and Christians in creating social harmony can be done when implementing openness when communicating with peers, positive attitudes during Halal binhalal activities and mutual cooperation activities, support when establishing Pancasila villages, equality when communicating without discriminating between religions and during maternal activities and empathy when one of the people is die. supporting factors for communication between Muslims and Christians in creating social harmony in Air Jamban Village, namely providing enlightenment, dialogue between religious communities, attending religious ceremonies and national days. Meanwhile, the inhibiting factor of communication between Muslims and Christians in creating social harmony in Air Jamban village is the existence of provocation and social prejudice.